2022
DOI: 10.3934/microbiol.2022003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of olive and date palm by-products on rumen methanogenic community in Barki sheep

Abstract: <abstract> <p>Rumen methanogens prevent the accumulation of fermentation gases in the rumen and generate methane that increases global warming and represents a loss in animals' gross energy. Non-traditional feed resources such as the by-products of date palm (<italic>Phoenix dactylifera</italic>) and olive (<italic>Olea europaea</italic>) trees have received attention to be used in animal feeding. This study evaluated the impact of non-traditional feed resources including ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“…Therefore understanding the effect of different animal diet on the rumen methanogens in different animal species progresses the global efforts to cut methane emission and improve of livestock sector. Concentrate level impact the ber to starch ratio, consequently, it impacted the animal feed intake, volatile fatty acids, and the relative abundance of the dominant methanogenic genera, which in the same line with the ndings of previous studies on feedlot bulls and sheep (Popova et al 2011;Rabee et al 2022). However, no available data on the effect of concentrates level on the methanogenic community in dromedary camels.…”
Section: Rumen Fermentationsupporting
confidence: 88%
See 2 more Smart Citations
“…Therefore understanding the effect of different animal diet on the rumen methanogens in different animal species progresses the global efforts to cut methane emission and improve of livestock sector. Concentrate level impact the ber to starch ratio, consequently, it impacted the animal feed intake, volatile fatty acids, and the relative abundance of the dominant methanogenic genera, which in the same line with the ndings of previous studies on feedlot bulls and sheep (Popova et al 2011;Rabee et al 2022). However, no available data on the effect of concentrates level on the methanogenic community in dromedary camels.…”
Section: Rumen Fermentationsupporting
confidence: 88%
“…Zhang et al (2017), on the other hand, investigated the effect of forage-to-concentrate ratios on rumen methanogen changes in Holstein heifers and discovered that the methanogenic community was dominated by the genus Methanobrevibacter and the relative abundances of rumen methanogenic genera were not signi cantly affected by dietary concentrate levels. Rabee et al (2022) showed a small decrease in the relative abundance of the genus Methanobrevibacter in sheep diets as a result of the substitution of concentrate feed combination with date palm byproducts and olive cake. According to Vaidya et al (2020), silage type (grass or maize silage) was positively linked with the abundance of the species Methanobrevibacter and Methanosphaera.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, rumen archaea uses fermentation gases such as hydrogen (H 2 ) and carbon dioxide (CO 2 ) besides methyl group derived from acetic acid, and format to generate methane (CH 4 ) [ 5 ]. Methane represents a 2–12% loss of the gross energy feed intake of host animal and it is one of the main reasons for climate change [ 5 , 6 ]. Rumen methanogens interact with H 2 producers and utilizers; therefore, modifying rumen microbial ecosystem is a main target for studies that aim to improve animal efficiency and decrease methane emission [ 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that the use of olive by-products did not negatively impact nutrients utilization, microbiota composition, and rumen fermentation variables, such as pH, ammonia and volatile fatty acids (VFA) concentrations ( Ruiz et al, 2004 ; Estaún et al, 2014 ; Pallara et al, 2014 ; Tzamaloukas et al, 2021 ). Differently by influencing the ruminal fermentation and the rumen pH, the increase of the content of linoleic acid, in both milk and meat, as well as change in the aromatic and microbiological profiles of milk are reported ( Chiofalo V. et al, 2020 ; Liotta et al, 2020 ; Foti et al, 2021 ; Tzamaloukas et al, 2021 ; Rabee et al, 2022 ). In fact, the high polyphenol content could modulate the rumen microbiota biodiversity and, consequently, affect the rumen metabolism, decreasing dietary protein degradation and fatty acid biohydrogenation by means of targeting specific groups of microorganisms ( Mannelli et al, 2018 ; Biondi et al, 2019 ; Milani et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%